Graduate Students "Show Their Work": Metalanguage in Dissertation Methodology Sections. (April 2017) - Pantelides, Kate L.
To address graduate writing pedagogy in technical communication, this article reports on a study of 14 award-winning dissertations in the field. By treating dissertations as cultural artifacts constitutive of the educational contexts in which they are authored, this study reads dissertation methodology sections as research narratives to understand how we prepare new scholars and to examine the changing nature of what we value in the field.